2017
DOI: 10.1016/j.asmart.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Regression modelling combining MRI measurements and patient anthropometry for patient screening and prediction of graft diameter in hamstring autograft arthroscopic ACL reconstruction

Abstract: BackgroundPrevious studies have associated anthropometric data and pre-operative hamstring tendon measurements to intraoperative graft diameter for hamstring autograft ACL reconstruction, although an integrated model has yet to be described. The aim of this study was to present such a predictive model for quadrupled semitendinosus (4-ST) and doubled semitendinosus-gracilis (4-STG) graft constructs combining anthropometry (height and weight) and preoperative measurements of tendon as predictors.MethodsACL recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…There is a growing body of literature attempting to use preoperative MRI to predict intraoperative HTA diameter. 16 , 19 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 Most of these studies have used ST and GT CSA measurements and correlated these relative to HTA diameter, with results ranging from weak ( r = 0.16) to strong ( r = 0.81), and often, the sum of ST and GT has been reported as showing the strongest correlation ( r values ranging from 0.42 to 0.93). 16 , 19 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 Our study found a moderate correlation with ST CSA ( r = 0.48) and combined ST-GT CSA ( r = 0.67) and a stronger correlation with GT CSA ( r = 0.71) in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of literature attempting to use preoperative MRI to predict intraoperative HTA diameter. 16 , 19 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 Most of these studies have used ST and GT CSA measurements and correlated these relative to HTA diameter, with results ranging from weak ( r = 0.16) to strong ( r = 0.81), and often, the sum of ST and GT has been reported as showing the strongest correlation ( r values ranging from 0.42 to 0.93). 16 , 19 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 Our study found a moderate correlation with ST CSA ( r = 0.48) and combined ST-GT CSA ( r = 0.67) and a stronger correlation with GT CSA ( r = 0.71) in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…However, considerable variability and heterogeneity have been reported for measurements of HTAs either individually or together, with most studies indicating a moderate correlation between MRI and intraoperative assessments. 16 , 19 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 35 Thus, there remains an overall lack of strong preoperative HTA diameter predictors. 33 …”
mentioning
confidence: 99%
“…These findings largely agree with previous papers that reported differences in notch characteristics between sexes (Charlton et al, ; Chandrashekar et al, ) as well as relationship to weight with respect to ACL‐injury risk (Whitney et al, ). Although height has been previously correlated with potential graft diameter in hamstring autograft reconstruction (An et al, ), its relationship to geometry of the fossa has not been previously reported. Similarly, significant interactions between age and sex, as well as weight and sex have not been previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…1). [30][31][32][33][34][35][36][37][38][39][40][41][42][43] The κ value assessing interreviewer agreement was substantial for title, abstract, and full-text screens, with values of 0.845 (95% CI ¼ 0.82-0.86), 0.930 (95% CI ¼ 0.92-0.94), and 0.975 (95% CI ¼ 0.96-0.98), respectively.…”
Section: Eligibility Assessment and Study Selectionmentioning
confidence: 99%